THE AUTONOMY OF THE ELDERLY FACING NURSING CARE: : INTEGRATIVE REVIEW - de Oliveira Santos, Arethusa; Mary Silva Souza, Rose (Health and Society, 2021)
The nursing team should promote adequate assistance to the elderly, prioritizing respect for their autonomy. The objective of this study is to evaluate in the existing literature the actions developed by the nursing performed to demonstrate the autonomy of the elderly. This is a descriptive, bibliographical study of the type integrative review. As a sample of articles in Portuguese, indexed in the portals SciELO, Virtual Health Library (VHL), Latin American and Caribbean Literature in Health Sciences (LILACS) and Google Academic, published between the years of 2012 and 2017. data, the articles will be categorized and inserted into tables or tables. It is hoped to help synthesize the evidence available in the literature on nursing care for the elderly regarding respect for their autonomy, and may help academics, professionals and researchers regarding the knowledge about the proposed theme, aiming for a quality nursing care, respecting autonomy of the elderly.